Qualitatively correct charge-transfer excitation energies in HeH + by time-dependent density-functional theory due to exact exchange Kohn-Sham eigenvalue differences - Gimon, Tino; Ipatov, Andrey; Heßelmann, Andreas; Görling, Andreas (Journal of Chemical Theory and Computation, 2009)
Time-dependent density-functional theory in the response regime is shown to yield qualitatively correct charge-transfer excitation energies in the system HeH+ if the exact Kohn-Sham exchange potential is employed to determine the Kohn-Sham orbitals and eigenvalues entering the time-dependent density-functional calculation. The employed exactexchange kernel is frequency-independent and, like conventional kernels in the local density approximation or in generalized gradient approximations, does not contribute to the chargetransfer excitation energy. This shows that it can be that not the exchange-correlation kernel, as generally believed, but the exchange-correlation potential plays the crucial role in the description of charge-transfer excitations. © 2009 American Chemical Society.